Boosting English Speaking Skills of 10th Grade Students at MA Tahfidzul Qur'an Darussalam Muhammadiyah Purbalingga through Task-Based Learning and Role Play on Descriptive Text in 2024 - Lestari, Endang; Al Arfan, Adam (Information Technology and Science (ITScience), 2025)
This research aims to enhance the English speaking skills of 10th-grade students at MA Tahfidzul Qur'an Darussalam Muhammadiyah Purbalingga through applying Task-Based Learning (TBL) and Role-play techniques, explicitly focusing on descriptive texts. As speaking remains a critical component of language proficiency, many students struggle with fluency and confidence in English communication. This study employs Classroom Action Research (CAR) with a three-cycle model comprising four key stages: planning, implementation, observation, and reflection, incorporating both qualitative and quantitative data collection techniques, such as pre-test and post-tests. By integrating TBL and Role Play, which emphasize interactive, student-centred learning and real-life context application, the research explores the effectiveness of these methods in improving students' speaking abilities. Preliminary results suggest that combining task-based activities and role-playing significantly increases student engagement, vocabulary acquisition, and speaking proficiency. Since the average student score before applying the Task-Based Learning method with the Role Play strategy was 6.5, the average score in Cycle I increased to 8.3 and in Cycle II, it further improved to 9.8. The findings provide valuable insights for educators looking to foster an engaging and effective learning environment in secondary schools.